The ratio of thioredoxin/Keap1 protein level is a predictor of distant metastasis in colorectal cancer. (December 2017) - Chang, Liang-Che; Fan, Chung-Wei; Tseng, Wen-Ko; Chein, Hui-Ping; Hsieh, Tsan-Yu; Chen, Jim-Ray; Hwang, Cheng-Cheng; Hua, Chung-Ching
Aim: Thioredoxin can reduce the cysteine group of Keap1 which could induce proteasome degradation of Nrf2, PGAM5 and Bcl-xL. Nrf2 regulates redox balance and Bcl-xL is anti-apoptotic and both are important in tumor progression.Methods: The protein levels of Keap1, thioredoxin, PGAM5 and Bcl-xL in the normal and tumor tissues of 64 subjects with colorectal cancer (CRC) were determined by western blot.Results: The tumor had higher Keap1 but lower PGAM5s and Bcl-xL protein expression than the normal tissue. The ratio of thioredoxin/Keap1 protein level in the normal (OR: 0.12; 95% CI: 0.02–0.83) or tumor tissue (OR: 0.17; 95% CI: 0.03–0.89) was a negative predictor for distant metastasis in CRC.Conclusion: Keap1-mediated degradation of PGAM5 and Bcl-xL may be active in CRC. The ratio of thioredoxin/Keap1 protein level may be useful for suggesting distant metastasis in CRC.